2019
DOI: 10.1248/bpb.b18-00561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pharmaceutical Formulation on the Mucosal Concentration of 5-Aminosalicylic Acid and <i>N</i>-Acetylmesalamine in Japanese Patients with Ulcerative Colitis

Abstract: The efficacy of 5-aminosalicylic acid (5-ASA) as the first-line therapy for ulcerative colitis (UC) is determined by the extent of drug delivery to the inflamed region. Moreover, differences among the various formulations influence delivery of the drug. In this study, we examined the clinical significance of colonic mucosal concentrations of 5-ASA and N-acetylmesalamine (Ac-5-ASA) in UC patients receiving a pH-dependent or time-dependent release formulation of 5-ASA. The subjects were 67 patients with UC who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…5‐ASA concentrations in both the sigmoid colon and the rectum were comparable among patients who received different 5‐ASA formulations. However, 5‐ASA concentrations tended to be lower in patients receiving time‐dependent 5‐ASA than patients receiving pH‐dependent 5‐ASA or multimatrix system 5‐ASA, and this was consistent with the results of previous studies 20,21 . In Japan, the manufacturer's maximum dose of time‐dependent, pH‐dependent, or multimatrix system 5‐ASA is 4.0, 3.6, and 4.8 g, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…5‐ASA concentrations in both the sigmoid colon and the rectum were comparable among patients who received different 5‐ASA formulations. However, 5‐ASA concentrations tended to be lower in patients receiving time‐dependent 5‐ASA than patients receiving pH‐dependent 5‐ASA or multimatrix system 5‐ASA, and this was consistent with the results of previous studies 20,21 . In Japan, the manufacturer's maximum dose of time‐dependent, pH‐dependent, or multimatrix system 5‐ASA is 4.0, 3.6, and 4.8 g, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…5-ASA concentrations were lower in patients using Pentasa than in patients using Asacol. 10 , 18 , 27 A recent study found that 5-ASA concentrations in the mucosa of the left hemicolon and rectum were higher in users of Mezavant and high 5-ASA concentrations were associated with a beneficial mucosal bacterial composition. 4 Furthermore, the mucosal 5-ASA concentration is correlated inversely to the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, 5-aminosalicylic acid (5-ASA or mesalazine), steroids, calcineurin inhibitors, etc., have been used to treat ulcerative colitis (UC) [ 1 , 2 ]. However, in recent years, numerous biological products have been developed, and treatment options for UC are expanding [ 3 ].…”
Section: Introductionmentioning
confidence: 99%